Empirical Insights into Capacity Building and Quality Assurance in Ethiopian Higher Education - Ramdhan, Tri Wahyudi; Kurniyah; Mowafg Abrahem Masuwd (At-Taqaddum, 2025)
This study investigates the policy dynamics and institutional mechanisms guiding capacity building in Ethiopia’s higher education within the framework of internationalisation and quality assurance. Drawing on a qualitative document review approach, the research analysed government policies, institutional strategies, and accreditation reports to assess how national directives align with global trends in higher education reform. The findings indicate that Ethiopian education policy increasingly incorporates internationalisation goals, such as academic mobility, collaborative research, curriculum benchmarking, and global quality standards. Strategic plans also highlight the importance of institutional autonomy and contextual relevance in Islamic education delivery. Despite this, the study reveals persistent challenges, including inadequate financial support, coordination gaps between agencies, and limited institutional readiness—especially among faith-based universities. Empirical evidence, including national audit reports and academic performance records, points to modest growth in faculty qualifications and research output in recent years, although progress varies across institutions. Thematic analysis suggests that while policy aspirations are clear, the operationalisation of these ambitions remains uneven and highly dependent on external funding and technical assistance. Moreover, the regulatory environment lacks specificity in addressing the dual demands of religious identity and global competitiveness. This paper contributes to ongoing debates on harmonising Islamic education with international academic standards in the Global South. It offers policy-level recommendations to strengthen institutional governance, resource mobilisation, and inter-agency collaboration. Ultimately, the study encourages rethinking capacity building not only as institutional enhancement but also as a culturally grounded and globally oriented transformation process in higher education systems.